2017
DOI: 10.1177/0194599817712215
|View full text |Cite|
|
Sign up to set email alerts
|

Antibiotic Prophylaxis in Clean‐Contaminated Head and Neck Surgery: A Systematic Review and Meta‐analysis

Abstract: Objective To determine the optimal duration and type of antibiotic prophylaxis in patients undergoing clean-contaminated resection for head and neck cancer. Data Sources Search strategies were created by a medical librarian, implemented in multiple databases, and completed in June 2016. Review Methods The population of interest was adults ≥18 years undergoing clean-contaminated head and neck surgery, intervention was postoperative antibiotic prophylaxis, comparator was duration and types of antibiotics used, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 42 publications
0
49
0
2
Order By: Relevance
“…Multiple studies evaluated the difference in SSI rate between short-and long-term prophylaxis. No statistically significant reduction in the SSI rate could be found in patients receiving prophylaxis for more than 5 days, compared with 1 day postoperatively [6,7,22,24,38,49]. Similarly, one RCT [4] could not demonstrate a beneficial effect in patients receiving prophylaxis for 3 days, compared with 1 day.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Multiple studies evaluated the difference in SSI rate between short-and long-term prophylaxis. No statistically significant reduction in the SSI rate could be found in patients receiving prophylaxis for more than 5 days, compared with 1 day postoperatively [6,7,22,24,38,49]. Similarly, one RCT [4] could not demonstrate a beneficial effect in patients receiving prophylaxis for 3 days, compared with 1 day.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, a large cross-sectional study showed that a postoperative antibiotic course for longer than 6 days did not further reduce the rate of SSIs (p = 0.08) [23]. Finally, a systematic review found no significant difference between 1 day and or 5 days of prophylaxis using various types of antibiotics including penicillins, cephalosporins, and clindamycin (p = 0.718, RR = 0.98, 95% CI 0.59-1.61) [49]. Sepehr et al [22], comparing cefazolin-metronidazole for less or more than 5 days, showed the same SSI rate in both groups (p = 0.06).…”
Section: Duration Of Postoperative Antibiotic Coursementioning
confidence: 96%
“…Current Australian guidelines do not recommend antibiotic prophylaxis in uncomplicated neck dissections (8). While some studies do not support use of prophylactic antibiotics in uncomplicated neck dissection (16), there is level 1a evidence (17) supporting the use of prophylactic antibiotics for 24 hours (18). For thyroidectomy/hemithyroidectomy, 48.93% of the surgeons did not prescribe any antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above work, a meta‐analysis of 340 patients in 4 RCTs by Vila et al further restricted the antibiotic administration window, comparing the risk of wound infection between 1 day vs 5 days of systemic antibiotic prophylaxis in clean‐contaminated head and neck surgery . All studies included clean‐contaminated oncologic resection of the primary tumor, and roughly a third of these cases included flap reconstruction as part of the surgery.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to the above work, a meta-analysis of 340 patients in 4 RCTs by Vila et al further restricted the antibiotic administration window, comparing the risk of wound infection between 1 day vs 5 days of systemic antibiotic prophylaxis in clean-contaminated head and neck surgery. 4 All studies included clean-contaminated oncologic resection of the primary tumor, and roughly a third of these cases included flap reconstruction as part of the surgery. Results showed that the overall pooled relative risk (RR) of wound infection was 0.98 (95% confidence interval [CI] 0.58-1.61; P = 0.718) in patients randomized to 1 day of postoperative prophylaxis compared to 5 days of prophylaxis.…”
Section: Literature Reviewmentioning
confidence: 99%